Reproducibility, relative validity and calibration of a food frequency questionnaire for adults - Neuciani Ferreira da Silva; Rosely Sichieri; Rosângela Alves Pereira; Regina Maria Veras Gonçalves da Silva; Márcia Gonçalves Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The purpose of the present study was to evaluate the reproducibility and relative validity and calibrate the dietary intake assessment of a food frequency questionnaire (FFQ) using a random sample of 195 adults aged 20 to 50 years from the Central-West Region of Brazil. The reference method used by the study was two 24-hour recalls (24hR) that provided energy-adjusted deattenuated food intake data for comparison purposes. With respect to reproducibility, the average weighted kappa was 0.43 and exact agreement was 41.5%. With regard to relative validity, correlation coefficients ranged from 0.32 (thiamin) to 0.51 (carbohydrates), with a mean of 0.41. Deattenuation and adjustment for energy intake decreased most correlation coefficients in relation to crude values. The food frequency questionnaire showed good reliability and moderate validity for most nutrients based on classification into quartiles of energy and nutrient intake. The calibrated means of the FFQ were more similar to the means estimated from the 24hR and showed lower standard deviation.